Metakognisi Guru Pendidikan Jasmani, Olahraga, dan Kesehatan di Sekolah Dasar dalam Pembelajaran - Wasis D. Dwiyogo (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
Abstract: The objective of this research is to describe metacognition of physical education, sport and health teacher of primary schools. The research is qualitative research utilizing interview and documentation as the data collection techniques. The research revealed three main findings, namely teacher’s metacognition in use when preparing, implementing, and evaluation of instruction, which have variation respectively into efforts to effectiveness, efficiency, and appeal instruction.